Analysis on desiccant coated heat exchangers based on a new performance parameter and thermodynamic model. (5th March 2023) - Pan, Q.W.; Xu, J.; Wang, R.Z.; Ge, T.S.
Highlights: Cooling power utilization efficiency is proposed for DCHE performance evaluation. Metal-organic framework DCHE has best performance. Silica gel DCHE performance is sensitive to operating conditions of air and water. Vapor compression air conditioner using DCHEs can improve efficiency. Abstract: Performance of traditional vapor compression air-conditioners can be improved by achieving sensible and latent loads decoupling via the use of desiccant coated heat exchangers (DCHEs). Performance evaluation of the DCHE is mainly based on its dehumidification capacity. However, extra loss of cooling power, caused by the switch of dehumidification and regeneration phases, has not been investigated in previous articles yet. Hence, assessment for cooling power utilization efficiency (CPUE) of the DCHE is essential. In this paper, a thermodynamic model based on the first law of thermodynamics is developed and the CPUE is proposed. Further, a fundamental parametric investigation is conducted to understand the effect of different desiccant types, structure parameters and operating conditions of air and water flow. The results show that ratio of metal to desiccant and outlet air temperature in dehumidification process are the key factors on the CPUE. CPUE of metal–organic framework DCHE is more than 0.95, which is superior to the other investigated desiccant types. Then, thermodynamics model of a vapor compression air conditioner is built to evaluate the electrical coefficient of performance of the system using DCHEs. The results for different desiccant types can achieve 6.5–8.2 at 15/40 °C evaporation/condensation temperatures.